2008
DOI: 10.3136/fstr.14.311
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microwave-assisted Hydrodistillation to Extract the Essential Oils from Satureja hortensis and Satureja montana

Abstract: Microwave-assisted hydrodistillation (MAHD) has recently been attended for the extraction of essential oils from medicinal plants/herbs. In this study, MAHD was investigated for the extraction of essential oils from two genotypes of savory (Satureja hortensis, so-called summer savory, and Satureja montana, socalled winter savory). Three levels of microwave power (220, 440 and 660 W) were selected for the extraction. MAHD resulted in a shorter extraction time compared to that in HD. Total extraction times at 66… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 19 publications
3
22
0
Order By: Relevance
“…Data showing the lengths of times needed by MAHD and HD to reach the extraction temperature (so-called induction Antibacterial properties of the essential oils from summer savory times) and those indicating the total recoveries of essential oils at different power levels were published elsewhere (21). For MAHD at 660 W, the extraction started much earlier than that for HD.…”
Section: Extraction Yieldmentioning
confidence: 99%
“…Data showing the lengths of times needed by MAHD and HD to reach the extraction temperature (so-called induction Antibacterial properties of the essential oils from summer savory times) and those indicating the total recoveries of essential oils at different power levels were published elsewhere (21). For MAHD at 660 W, the extraction started much earlier than that for HD.…”
Section: Extraction Yieldmentioning
confidence: 99%
“…Over the last few years, more laboratories have successfully applied microwave-assisted extraction (MAE) [2,3] and in situ microwave-generated hydrodistillation (MGH) [4], which are both now well recognized as innovative green and efficient techniques [5]. Dielectric heating is a nonclassical energy source that is capable of reducing extraction times because of its selective volumetric heating that also gives excellent product quality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The required time to reach the boiling point of water at 540 W was nearly one-fourth of that at 180 W. After 20 minutes of operation, the extraction yield at 540 W (1.53%, w/w) was about five times more than that at 180 W (0.31%, w/w). Meanwhile, the extraction yield for 540 W after 45 minutes of operation was the same as that obtained in 60 minutes at 360 W [22]. In another study, Özek et al (2005) extracted essential oils of three endemic Turkish Heracleum species by different techniques.…”
Section: Resultsmentioning
confidence: 91%
“…They found that for the same extraction yield, the time required for microwave-assisted hydro-distillation was one-fourth of that for hydro-distillation [21]. Rezvanpanah et al (2008), extracted essential oils from Satureja hortensis and Satureja montana using microwave-assisted hydro-distillation, where the extraction time was reduced significantly as the microwave power was changed from 220 to 660 W. The difference in the extraction yield at 180 and 540 W seemed to be more pronounced during the first 2 hours of extraction. The required time to reach the boiling point of water at 540 W was nearly one-fourth of that at 180 W. After 20 minutes of operation, the extraction yield at 540 W (1.53%, w/w) was about five times more than that at 180 W (0.31%, w/w).…”
Section: Resultsmentioning
confidence: 99%